Skill Improving Ways in Traditional Song Performing - Talaboyev, Azizjon (European Journal of Life Safety and Stability (2660-9630), 2021)
This article highlights the methodological foundations of the process of formation of performing skills of students of cultural institutions, the specificity of this process. The most popular modern methods of vocal training of performers are presented, the short analysis of the most famous vocal schools of Russia and abroad is given. Considers the current state of the vocal training of future specialists in the vocals. Recommendations on optimization of process of vocal preparation of students of higher education institutions are given. The concepts of "performing skills", "performing", "vocal skills" and the meaning of these concepts in the system of training a vocalist in high school are revealed. Named the experience of outstanding vocal teachers of different eras and researchers in the field of vocal performance. The article contains a list of professional and universal competences of a modern high school teacher according to the theory of modern researchers. Considered system and active approaches to teaching vocal.